Integration of a community-based harm reduction program into a safety net hospital: a qualitative study - Ghulam Karim Khan; Leah Harvey; Samantha Johnson; Paul Long; Simeon Kimmel; Cassandra Pierre; Mari-Lynn Drainoni (BMC, 2022)
Abstract Background Community-based harm reduction programs reduce morbidity and mortality associated with drug use. While hospital-based inpatient addiction consult services can also improve outcomes for patients using drugs, inpatient clinical care is often focused on acute withdrawal and the medical management of substance use disorders. There has been limited exploration of the integration of community-based harm reduction programs into the hospital setting. We conducted a qualitative study to describe provider perspectives on the implementation of a harm reduction in-reach program. Methods We conducted 24 semi-structured interviews with providers from three different primary work sites within a safety net hospital in Boston, MA, in 2021. Interviews explored perceived facilitators and barriers to the implementation of the harm reduction in-reach program in the hospital setting and solicited recommendations for potential improvements to the harm reduction in-reach program. Interviews were analyzed using an inductive approach that incorporated principles of grounded theory methodology to identify prevailing themes. Results Twenty-four participants were interviewed from the harm reduction in-reach program, inpatient addiction consult service, and the hospital observation unit. Thematic analysis revealed seven major themes and multiple facilitators and barriers to the implementation of the harm reduction in-reach program. Participants highlighted the impact of power differences within the medical hierarchy on inter-team communication and clinical care, the persistence of addiction-related stigma, the importance of coordination and role delineation between care team members, and the benefits of a streamlined referral process. Conclusions Harm reduction programs offer accessible, patient-centered, low-barrier care to patients using drugs. The integration of community-based harm reduction programs into the inpatient setting is a unique opportunity to bridge inpatient and outpatient care and expand the provision of harm reduction services. Trial registration: Not applicable.